Scene recognition by semantic visual words - Farahzadeh, Elahe (2015)
In this paper, we propose a novel approach to introduce semantic relations into the bag-of-words framework. We use the latent semantic models, such as latent semantic analysis (LSA) and probabilistic latent semantic analysis (pLSA), in order to define semantically rich features and embed the visual features into a semantic space. The semantic features used in LSA technique are derived from the low-rank approximation of word–image occurrence matrix by singular value decomposition. Similarly, by using the pLSA approach, the topic-specific distributions of words can be considered dimensions of a concept space. In the proposed space, the distances between words represent the semantic distances which are used for constructing a discriminative and semantically meaningful vocabulary. Position information significantly improves scene recognition accuracy. Inspired by this, in this paper, we bring position information into the proposed semantic vocabulary frameworks. We have tested our approach on the 15-Scene and 67-MIT Indoor datasets and have achieved very promising results.